Analysis of exhaust emissions of natural gas engine by using response surface methodology - Saidur, Rahman; Jahirul, M.I.; Hasanuzzaman, M.; Masjuki, Haji Hassan (Asian Network for Scientific Information, 2008)
Experiments were conducted to investigate the engine's emission at the different operating conditions. The tests were conducted by varying the engine speed, throttle opening and operating time. During the experimental investigation, the operating variables were varied (engine speed from 1500 to 2500 rpm; throttle percentage from 25 to 36 and operating time from 2.5 to 5 min) according to the experimental schedule set up. These emission models reveal the effects of each parameter's significance and adequacy for the design range which evaluated using ANOVA F-test. The effects of each parameter in emission response are studied through the response model. From the comparative evaluation of the experimental results for the different operating conditions, it is revealed that there is an influence of the engine speed, throttle position and operating time. From the analysis, it is concluded that emissions are more affected on engine speed and throttle position.